ANALISIS VARIABEL YANG MEMPENGARUHI PERKEMBANGAN PRODUKSI GULA MERAH TEBU DI DESA SUKOLILO KECAMATAN WAJAK KABUPATEN MALANG (Analysis Of Factors Influencing of Brown Sugar Production & Income In Sukolilo Village, Wajak District, Malang Regency) - FITRIYANI, EMA KURNIA; GUNAWAN, CAKTI INDRA; SETIAJI, JATMIKO (Universitas Mulawarman (University of Mulawarman), 2025)
The main problem in the development of cane brown sugar production is that the factors of adequate availability of raw materials, labor, business/initial capital & length/production time greatly influence the sustainability of the business carried out by brown sugar craftsmen. This research aims to determine the variables that influence the development of household brown sugar sugar cane production businesses cultivated by craftsmen. The sampling method was used by census with a total of 30 brown sugar cane craftsmen as a sample. The data collected is primary data & secondary data. The analysis method used is multiple linear analysis with SPSS 21 software tools. The results of the research show that the variables of labor & raw materials have a significant effect on the production of brown sugar cane household businesses. Partially, it shows that the raw material & labor variables have a positive & significant influence on the production of cane brown sugar & simultaneously, through the F test, all variables have a significant effect on the development of cane brown sugar production.